Clinical Manifestations of Nontyphoid Salmonellosis in Children Younger than 2 Years Old—Experiences of a Tertiary Hospital in Southern Taiwan - I-Fei Huang; Chih-Hsiang Kao; Wei-Yang Lee; Ming-Fang Chang; Yao-Shen Chen; Kuan-Sheng Wu; Hong-Hsiang Hu; Kai-Sheng Hsieh; Christine C. Chiou (Pediatrics and Neonatology, 2012)
Few published studies have explored the clinical manifestations of nontyphoid salmonellosis in children <2 years of age. The aim of this study was to investigate the clinical manifestations, microbiological features, complications, fecal excretion time, and responses to treatment in children <2 years of age with nontyphoid salmonellosis. Methods: Between January 2005 and December 2009, pediatric patients who were admitted to Kaohsiung Veterans General Hospital with positive cultures for nontyphoid Salmonella were enrolled. The following data were recorded: demographic, clinical, and microbiological features, underlying diseases, treatment regimen, complications, responses to treatment, and fecal excretion time. The clinical manifestations were compared between patients <2 years of age and patients >2 years of age. Results: Of a total 279 enrolled patients, 179 were >2 years of age. Compared with the patients who were ≥2 years of age, patients <2 years of age demonstrated a significantly higher incidence of bloody stool, mixed infection, extraintestinal infection, longer course of antibiotics, longer course of diarrhea after admission, and more days spent in the hospital. The rates of insusceptibility of nontyphoid Salmonella to ampicillin, chloramphenicol, trimethoprim/sulfamethoxazole, ceftriaxone, and ciprofloxacin in patients <2 years of age were 37.87%, 29.09%, 23.73%, 3.26%, and 2.25%, respectively. Younger patients were generally more susceptible to antibiotics than patients ≥2 years of age, although this result was not statistically significant. Conclusion: The clinical manifestations of nontyphoid salmonellosis are more severe in younger children <2 years of age than older children. Local susceptibility patterns could serve as a guide for the prescription of antibiotics by clinicians.